Environmental enrichment as a therapeutic strategy against methamphetamine induces depressive behaviors in mice - Hammad Ismail; Syed Abdul Rafay; Talha Yaseen; Dania Khalid; Muhammad Zeeshan Bhatti; Salman Shahzad; Sabir Shahzad; Samreen Saleem; Abdur Rahman; Modhi O. Alotaibi; Areej Turkistani; Bushra Akram; et al. (PLoS ONE, 2025)
Methamphetamine (METH) abuse is associated with addiction, emotional dysregulation, motor impairments, cognitive deficits, and depressive symptoms, which are exacerbated by stress and social isolation. This study investigated the therapeutic potential of combined treatment and environmental enrichment in METH withdrawn mice. Behavioral, biochemical and neurochemical outcomes were evaluated. Post-treatment results demonstrated: motor and exploratory behavior via OFT (open field test) mobility increased to from 32.37 meters (withdrawal group) to 59.52 meters, anxiety reduction indicated in EPM (elevated plus maze test) open arm rose from 33.2 to 74.2 sec, while cognitive improvement by MWM (morris water maze test) escape latency decreased from 225.4 to 127.4 sec in hidden platform trial. Moreover, memory and exploration activity were determined by NOR (novel object recognition test) and HBT (hole board test) which showed enhanced novel object exploration (16.4 vs 5 sec) and exploratory behavior (17.6 explored areas vs 8.6). Social interaction time increased to 41.64 sec, and light-dark compartment preference improved to 68.4%. Biochemical analysis revealed elevated antioxidants enzymes activity POD (peroxidase) (0.178 U/min) SOD (superoxide dismutase) (0.82 U/mg protein) and CAT (catalase) (3.6 U/min) indicating improved oxidative stress resilience. Neurotransmitters restoration was observed with serotonin (0.21 µg/mg) and dopamine (0.46 µg/mg) levels rebounding from negligible withdrawn group. These findings demonstrate that combined treatment and enriched environment robustly accelerate functional recovery in METH-withdrawn mice, suggesting a promising strategy for mitigating addiction-related deficits.